"Evaluación de cuatro ectractos vegetales en diferentes dosis para el combate del gusano taladrador del fruto (Disaphania nitidalis L.), en el cultivo de pepino (Cucumis savtivus L.), en la zona de El Empalme". - Villigua Villigua, Edy Gabriel (2015)
This test was performed on the farm of Mr. Solomon Villigua, located in the village of El Empalme Guayas province in the months of January to March 2015 during the rainy season. The general objective of this research was: To determine the best bio-insecticides control insect pests that present positive responses at the level of production using plant extracts with insecticidal property and a specific objective: To identify the specific bioinsecticida to control the worm driller of the fruit of the cucumber applying different dose, to study the morphological behavior of the cucumber cultivation in function to the application of the four bioinsecticidas, to carry out the economic analysis, in function of benefits and costs for hectare...................................